Extragastrointestinal Stromal Tumor: A Differential Diagnosis of Compressive Upper Abdominal Tumor - Clara Kimie Miyahira; Miguel Bonfitto; Jéssyca Fernanda de Lima Farto; Annelise de Figueiredo Calili; Nathalia Rabello da Silva Sousa; Ana Paula de Figueiredo Calili (Case Reports in Surgery)
Introduction. Extragastrointestinal stromal tumors (EGIST) are rare mesenchymal tumor lesions located outside the gastrointestinal tract. A rare compressing tumor with difficult diagnosis is reported. Presentation of the Case. A male patient, 63 years old, was admitted in the emergency room complaining of stretching and continuous abdominal pain for one day. He took Hyoscine, with partial improvement of symptoms, but got worse due to hyporexia, and the abdominal pain persisted. The patient also reported early satiety and ten-pound weight loss over the last month. Discussion. EGIST could be assessed by CT-guided biopsy, leading to diagnosis and proper treatment with surgical resection or Imatinib. Conclusion. This case report highlights the importance of considering EGIST an important differential diagnosis of compressing upper abdominal tumors.